Plate I: Benzol (Encyclopædia of Chemistry, Theoretical, Practical, and Analytical, as Applied to the Arts and Manufacturers, Vol. I and II, 1877)
Cylindrical stills for the manufacture of benzene. Now termed benzene, "benzol" is a hydrocarbon first discovered by Michael Faraday in 1825, in the liquid which resulted from the compression of illuminating gases produced by the destructive distillation of oil. The benzene manufactured was used for dye production.
Keywords: Benzene; Manufacturing processes; Chemistry, Technical